1999
DOI: 10.1590/s0100-879x1999001100014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the injection of an extract of Ascaris suum on macrophage activation during the early phase of Mycobacterium bovis BCG infection in C57Bl/6 mice

Abstract: Injection of an Ascaris suum extract (Asc) affects both the humoral and cellular immune responses to unrelated antigens when it is coadministered with these antigens. In the present study we evaluated the effect of Asc on macrophage activation in the early phase of Mycobacterium bovis BCG (Pasteur strain TMCC 1173) infection in C57Bl/6 mice. C57Bl/6 mice were injected intraperitoneally (ip) with 0.1 mg BCG (BCG group) or BCG plus 1 mg Asc (BCG + Asc group). The peritoneal exudates were obtained at 2, 7 and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…The differences between our findings and that of Ferreira et al [25] may be that they evaluated the ability of mice injected with Ascaris suum extract to control mycobacterial infection during the first week of infection and our analysis was made at the later stage. This may indicate that the impact of exposure to worm antigens and/or infection with worms on the immune response to subsequent infections depends on the stage of the infection.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The differences between our findings and that of Ferreira et al [25] may be that they evaluated the ability of mice injected with Ascaris suum extract to control mycobacterial infection during the first week of infection and our analysis was made at the later stage. This may indicate that the impact of exposure to worm antigens and/or infection with worms on the immune response to subsequent infections depends on the stage of the infection.…”
Section: Discussioncontrasting
confidence: 77%
“…Ferreira et al [25] have shown that early stage responses to mycobacterial challenge can be enhanced by injection of mice with Ascaris suum extract. However, in the current study chronic infection with helminth parasite S. mansoni was associated with reduced ability to control mycobacterial infection accompanied by impaired cellular responses to mycobacteria antigen.…”
Section: Discussionmentioning
confidence: 99%
“…52 The life-cycle of Trichinella spiralis involves an intestinal phase, followed by encystment in skeletal muscle; suppression of the IgA response to cholera toxin 53 and to hepatitis B immunisation 54 has been demonstrated during the intestinal, but not the muscle, stages of the life-cycle. While these experiments demonstrate suppressive effects, intraperitoneal injection of Ascaris extract concurrently with BCG has been shown to enhance macrophage activation and suppress BCG replication 55 and a protein from the filarial worm Onchocerca volvulus shows promise as an adjuvant for influenza vaccine. 56 Together, studies in mice show that helminth infections have important potential to supress vaccine responses, but that helminth species, stage of life-cycle, timing of helminth exposure and treatment, and characteristics of the vaccine may be important determinants of the outcome and that specific helminth molecules may actually have enhancing effects.…”
Section: Worms and Vaccinesmentioning
confidence: 99%
“…This dose of BCG has been commonly used by several authors working with mice [22][23][24] . It has been reported that BCG establishes itself in the spleen of mice over 15-20 days [25][26][27] . Hence, 15 days postinoculation with BCG, we infected mice with 252 μL of JEV (100 LD 50 ) or PBS by intracranial (i.c.)…”
Section: Jev Infection and Inoculation Of Mice With Bcgmentioning
confidence: 99%
“…After 15 days (corresponding to the time reported for BCG to establish itself in mice [25][26][27] ), we challenged the mice with a virulent strain of 100 LD 50 JEV or PBS as per the schematic shown in Figure 1 .…”
Section: Bcg Delays the Onset Of Clinical Symptoms Post-jev Infectionmentioning
confidence: 99%